The role of the supportive teacher in improving the teaching learning process from the point of view of teachers of the first three grades in the Northwestern Badia schools (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to investigate the role of the supporting teacher in classroom management in the light of modern educational trends; Where the descriptive analytical approach was used by reviewing studies and literature related to research variables and preparing research tools, and the research sample consisted of (145) principals of government schools affiliated to the Directorate of Education of the Northwest Badia in the Hashemite Kingdom of Jordan, they were chosen by a simple random sample method, and the research tools were From the work of a questionnaire to measure the role of the supportive teacher in classroom management in the light of modern educational trends, and the study was applied in the second semester of 2022-2023. The results showed that the role of the supportive teacher in classroom management in the light of modern educational trends came with a high degree of appreciation, and the results did not show the presence of statistically significant differences at the significance level (a = 0.05) for the reality of the teacher’s practice of a course in classroom management due to the variable (sex, qualification scientific).